Peningkatan Kreativitas dan Hasil Belajar Sejarah Indonesia Kuno Melalui Optimalisasi Model Pemecahan Masalah Kreatif Dalam Proses Belajar Mengajar (PBM) di Prodik Sejarah FKIP – UNS - Akhmad Arif Musadad (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
The objective of research is to improve the creativity and classic Indonesian history learning achievement through optimizing the creative problem solving model in teaching-learning process in History Study Program of FKIP UNS. This study was carried out using classroom action research. The subject of research was the students of History Study Program attending classing Indonesian history course. Meanwhile the object was the teaching-learning process activity, including: lecturer’s teaching activity, students’ creativity and learning achievement. This research was carried out using collaborative participative approach between the in-charge-of lecturer, assisting lecturer (researcher), and the student so that sharing occurs in each stage of activity. This research was done using cyclical analysis process encompassing four stages of activity: planning, acting, observing, and reflection. This research was implemented in two cycles: cycle I as the implementation of action, and cycle II as improvement. The result of this research shows that from one cycle to another the student’s creativity and learning achievement improves. It is reflected from: the improvement of students discipline in utilizing learning time, capability of looking for and collecting the source, capability of identifying, formulating, and solving the problem, idea generation, students’ idea.ABSTRAK Penelitian ini bertujuan untuk meningkatkan kreativitas dan hasil belajar mahasiswa tentang sejarah Indonesia kuno melalui optimalisasi model pemecahan masalah kreatif dalam pembelajaran di Program Studi Pendidikan Sejarah FKIP UNS. Metode penelitian menggunakan penelitian tindakan kelas. Subyek penelitian meliputi mahasiswa Program Studi Pendidikan Sejarah yang menempuh mata kuliah sejarah Indonesia kuno, dengan obyek: aktivitas mengajar dosen, kreativitas dan hasil belajar mahasiswa. Pendekatan penelitian ini dilaksanakan melalui partisipatif kolaboratif antara dosen pengampu, dosen pendamping (peneliti), dan mahasiswa. Penelitian dilakukan dengan proses pengkajian berdaur yang meliputi tahap perencanaan tindakan, pelaksanaan, pengamatan, dan refleksi. Penelitian ini dilaksanakan dalam dua siklus, yaitu siklus I sebagai implementasi tindakan dan siklus II sebagai perbaikan. Hasil penelitian menujukkan bahwa dari satu siklus ke siklus berikutnya kreativitas dan hasil belajar mahasiswa semakin meningkat. Hal itu tercermin dari peningkatan kedisiplinan mahasiswa dalam memanfaatkan waktu belajar, kemampuan mencari dan mengumpulkan sumber, kemampuan mengidentifikasi, merumuskan dan memecahkan masalah, dan tumbuhnya ide, gagasan dari mahasiswa.